2022
DOI: 10.3390/molecules27123925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Retentive Element Materials on Retention of Mandibular Implant-Retained Overdentures

Abstract: This study aimed to examine the retentive characteristics of each retentive element material and the effects from thermocycling using the two implant-retained mandibular overdenture model. Two stud abutments and three retentive element materials; nylon, polyetheretherketone (PEEK) and polyvinylsiloxane (PVS) were used in this study. Four tested groups, with a total of 40 overdentures, were fabricated, including a Locator® abutment with nylon retention insert (NY), Novaloc® abutment with PEEK retention insert (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Biomaterials used to fabricate the retentive elements also play vital role in influencing the retention of the overdenture. Chindarungruangrat et al [ 13 ] studied the retentive force of retentive element materials using three retentive element materials: nylon, polyetheretherketone (PEEK), and polyvinyl siloxane (PVS). The retentive force (N) was measured before thermocycling and at 2500, 5000, and 10,000 cycles after thermocycling and it was concluded that the retentive element materials tend to lose their retentive capability because of thermal undulation and water dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Biomaterials used to fabricate the retentive elements also play vital role in influencing the retention of the overdenture. Chindarungruangrat et al [ 13 ] studied the retentive force of retentive element materials using three retentive element materials: nylon, polyetheretherketone (PEEK), and polyvinyl siloxane (PVS). The retentive force (N) was measured before thermocycling and at 2500, 5000, and 10,000 cycles after thermocycling and it was concluded that the retentive element materials tend to lose their retentive capability because of thermal undulation and water dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Greater retentive strength may also affect the longevity of the flexible matrix [6][7][8][9]. Maximum studies evaluated the retentive strengths of 2IMO after simulated function and very few evaluated the stresses at baseline without age simulation [9,[11][12][13][14][15]. e attachments are serviceable from the first day of their usage in mouth; hence, the present study evaluated their retentive strength without any age simulation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations